Interview with Maria Manuela dos Reis Martins: considerations on Urban Archaeology landscape and territory - Martins, Maria Manuela dos Reis (Romanitas - Revista de Estudos Grecolatinos, 2015)
Interview with Maria Manuela dos Reis Martins.